Analisis Perbandingan Ekstrak Daun Jambu Biji (Psidium guajava L.) Terhadap Pertumbuhan Bakteri Propionibacterium acnes dan Staphylococcus aureus Dengan Menggunakan Metode Sumuran - Risman Tunny; Epi Dusra; Annisatul Khoiriyah Kaplale; Jayanti Djarami; Maritje.S.J. Malisngorar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Acne is a disease on the surface of the skin of the face, neck, chest, and back that appears when the oil glands in the skin are too active so that the skin pores will be clogged by excessive fat deposits. Guava leaves contain secondary metabolites, consisting of tannins, alkaloids, flavonoids, saponins. This study aims to identify the content of secondary metabolites in guava leaf extract (Psidium guajava L.), test the antibacterial activity of ethanol extract of guava leaves (Psidium guajava L.) against the growth of Propionibacterium acnes and Staphylococcus aureus bacteria, and analyze the comparison of the effectiveness of guava leaf extract (Psidium guajava L.) against the growth of the two test bacteria. This type of research is laboratory experimental. The methods used for this study: preparation of materials, extraction of samples by maceration method, phytochemical screening test, testing antibacterial activity using the pitting method and analyzing data. The screening test results of guava leaf extract (Psidium guajava L.) showed the presence of alkaloid, flavonoid, tannin and saponin compounds. The results of the inhibition test on guava leaf extract with a high concentration of 115% have the largest diameter of 17.5 mm against Staphylococcus aureus compared to Propionibacterium acnes bacteria with an inhibition diameter of 16 mm. The results of the Mann-Whitney statistical test showed a p-value of 0.077 so it can be concluded that there is no comparison of the effectiveness of guava leaf extract (Psidium guajava L.) against the growth of Propionibacterium acnes and Staphylococcus aures bacteria.